(untitled) (Practitioner Research, 2020)
Users of accounting information crave of quality financial reporting, by emphasising on the quality of the auditors neglecting the attribute of the managers.This study investigates the influence of managerial abilities on financial reporting in Nigerian listed non-financial sectors. The time series research design was employed by selecting 40 non-financial institutions as sample size between 2010 and 2017. Secondary data obtained from the financial report were analysed using correlation and logistic regression. It was found that managerial ability has an inverse relationship on financial reporting quality, which is consistent with the agency theory.The finding implied that managers employ their ability to income smoothing for the benefit of the organisation rather than the interest of the shareholders.